Challenges facing human resources management and mechanisms for their solutions - An applied study on the Ministry of Labor and Social Development Branch, Asir Region – - Masdar, Youssef Abdullah (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the most important challenges facing the human resources management in the Ministry of Labor and Social Development in the Asir region, and to try to develop solutions and remedial proposals for these challenges. In order to achieve these goals; The study adopted the descriptive and analytical approach. The researcher also designed a questionnaire as a main tool for collecting the necessary data, which was applied to a sample of workers in the Ministry of Labor and Social Development in Asir region amounting to (130) individuals. The study reached several results, the most important of which are: There are high challenges facing the human resources management in the Ministry of Labor and Social Development in Asir Region, and these challenges are represented in five basic ones: (human, administrative, social, economic and legal challenges). The results of the arithmetic averages have shown There is agreement among the study sample that there is a difference in the degree of importance and severity of the challenges facing the human resources management in the Ministry of Labor and Social Development in the Asir region, where the economic challenges ranked first, with the mean of the arithmetic reaching 3.66, followed by the legal challenges, where the mean was 3.56, then the challenges. The social mean, where the arithmetic mean reached 3.51, followed by the administrative challenges, where the arithmetic mean reached 3.38, and in the last place the human challenges, where the arithmetic mean reached 3.33.